PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKUTURAL NUMBERED HEADS TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII.2 SMP NEGERI 3 TAMBANG - Mariana '; Yenita Roza; Putri Yuanita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research was based on the students’ mathematic achievement at class VIII.2 SMPN 3 Tambang under the Minimum Mastery Criteria with percentage of 30%, there are only 9 out of 30 students who achieve the Minimum Mastery Criteria on the main discussion about relevancy with equation of circle tangent and then the learning process still teacher center. This research is classroom action research. This research aims to improve learning process and students’ mathematic achievement at class VIII.2 SMPN 3 Tambang through the implementation cooperative learning model of structural Numbered Heads Together. The subject of the research are 30 students from class VIII.2 SMPN 3 Tambang consisting 14 male and 16 female students with the heterogeneous academic level. The instruments of data collection in this research were observation sheets and students Mathematic tests. The observation sheets were analyzed in qualitative desciptive, while the students’ Mathematic tests were analyzed in quantitative descriptive. The qualitative descriptive showed an improvement of learning process prior to the action on the first and second cycle. The results of this research showed an increasing number of students’ mathematic achievement from the basic score with the percentage 30% to 53,33% on the first daily test and 83,33% on the second daily test. Based on the result of this research can be concluded that the implementation of Cooperative Learning Model of structural approach Numbered Heads Together can improve students’ mathematic achievement at class VIII.2 SMPN 3 Tambang in the second semester academic years 2015/2016.KeyWord : Students’ Mathematic Achievement, Cooperative Learning Model Structural Approach of Numbered Heads Together, Classroom Action Research.